2021
DOI: 10.1101/2021.03.15.435408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intertissue mechanical interactions shape the olfactory circuit in zebrafish

Abstract: While the chemical signals guiding neuronal migration and axon elongation have been extensively studied, the influence of mechanical cues on these processes remains poorly studied in vivo. Here, we investigate how mechanical forces exerted by surrounding tissues steer neuronal movements and axon extension during the morphogenesis of the olfactory placode in zebrafish. We mainly focus on the mechanical contribution of the adjacent eye tissue, which develops underneath the placode through extensive evagination a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…Our targeted manipulations of RA levels suggest that RA production and diffusion from the eye acts as a critical pro-neurogenic influence on the composition and function of neurogenic neighborhoods. Interestingly, mechanical interactions between the developing eye and OE were recently shown to affect OE morphology 49 , which, together with our results, indicate significant mechanochemical interplay between the developing eye and nose. Sharp changes in Notch and RA signaling have been previously shown to attenuate noise in signal transduction resulting from stochastic variation and fluctuations in gene expression across space and time 4,5,28 .…”
Section: Neurogenic Neighborhoods Assemble and Expand To Facilitate O...supporting
confidence: 84%
“…Our targeted manipulations of RA levels suggest that RA production and diffusion from the eye acts as a critical pro-neurogenic influence on the composition and function of neurogenic neighborhoods. Interestingly, mechanical interactions between the developing eye and OE were recently shown to affect OE morphology 49 , which, together with our results, indicate significant mechanochemical interplay between the developing eye and nose. Sharp changes in Notch and RA signaling have been previously shown to attenuate noise in signal transduction resulting from stochastic variation and fluctuations in gene expression across space and time 4,5,28 .…”
Section: Neurogenic Neighborhoods Assemble and Expand To Facilitate O...supporting
confidence: 84%
“…119 Ablation of Müller Glia cells in the zebrafish retina revealed their role as mechanosensitive springs holding the retina together in a compressive way. 129 Recently, the role of mechanical interaction of the developing eye field with the adjacent tissue has been probed in vivo 53 with the finding, that a mechanical contact of the forming optics vesicle to the adjacent tissue is required for proper development. Beyond mechanical manipulation, the technology has been used to characterize neuronal circuits in the zebrafish brain 130 and has revealed that the mechanosensitive ion channel Piezo1 also controls neuron regeneration.…”
Section: Laser Microdissectionmentioning
confidence: 99%
“…As a result, the connection between optic vesicle and underlying surface ectoderm has identified as crucial for optics cup morphogenesis, raising the question how external mechanical signals from other tissues are required for proper retina development. 42,[53][54][55] There are several benefits of mapping cell-level models onto continuum descriptions. One benefit is experimental testing of models.…”
Section: From Vertex Models To Continuum Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations